Extensive Sex- and/or Hormone-Dependent Expression of Rat Housekeeping Genes - Das, Rajat K. (2012)
Using a commercially available qRT-PCR array designed to measure the expression of 32 rat housekeeping genes, we found that the levels of 5 of the genes were sexually dimorphic, 22 genes were over-expressed and one under-expressed in multi-hormone deficient hypophysectomized rats of both sexes. Only 3 genes fulfilled the stability criteria determined by geNorm and NormFinder as suitable housekeeping genes. Normalizing qRT-PCR data with either of these 3 genes alone, the geometric means of any 2 of the genes, or even the geometric mean of all 3 genes, produced similar results. In contrast, application of unproven housekeeping genes could lead to erroneous conclusions, having found that IGF-1 mRNA levels could be calculated as either dramatically male- or female-predominant depending upon the choice of housekeeping gene. Accordingly, it is essential to validate the constancy of housekeeping genes under every experimental condition. (This research protocol was approved by the university’s Institutional Animal Care and Use Committee.)